ҚАРАҚАЛПАҚ ТИЛИНДЕ СОМАТИЗМЛЕР МЕНЕН КЕЛГЕН ФЕЙИЛ ФРАЗЕОЛОГИЗМЛЕР - Қурбанбаева, Б.; Ерлепесова, Д. (FAN va JAMIYAT, 2016)
The article is devoted to the study of verbal phraseologisms-somathizms. It is emphasized that phraselogisms-somathizms denoting hames of parts of a human body are often used in the Karakalpak language. These phraseologisms belong to different parts of speech.